Sorting and local wage and skill distributions in France - Pierre-Philippe Combes; Gilles Duranton; Laurent Gobillon; Sébastien Roux (Institute for the Study of Labor (IZA), 2012)
This paper provides descriptive evidence about the distribution of wages and skills in denser and less dense employment areas in France. We confirm that on average, workers in denser areas are more skilled. There is also strong over-representation of workers with particularly high and low skills in denser areas. These features are consistent with patterns of migration including negative selection of migrants to less dense areas and positive selection towards denser areas. Nonetheless migration, even in the long run, accounts for little of the skill differences between denser and less dense areas. Finally, we find marked differences across age groups and some suggestions that much of the skill differences across areas can be explained by differences between occupational groups rather than within.
urn:nbn:de:101:1-2012080812468
Keywords: J31; J61; R12; R23; 330; sorting; wage distribution; skill distribution; Regionale Lohnstruktur; Qualifikation; Räumliche Verteilung; Bevölkerungsdichte; Frankreich